1991
DOI: 10.1093/ajcn/54.3.526
|View full text |Cite
|
Sign up to set email alerts
|

A new procedure to assess the energy requirements of lactation in Gambian women

Abstract: The combined 24-h energy expenditure (24-h EE) of mother and child was measured with a respiratory chamber (indirect calorimeter) in a group of 16 lactating Gambian women and was compared with that of a control group of 16 nonpregnant, nonlactating (NPNL) Gambian women. Breast-milk production (738 +/- 47 g/d: mean +/- SE) was adequate to allow a normal rate of growth of their 2-mo-old babies (28.0 +/- 2.4 g/d). The combined 24-h EE (mother and child) was higher (8381 +/- 180 kJ/d. P less than 0.001) than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Conflicting results of lower fasting respiratory quotient in lactating compared with nonlactating women (0.82 and 0.85, respectively) (7), as well as no significant differences in respiratory quotient during lactation (10,15,39) have been published.…”
Section: Energy Expenditure During Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicting results of lower fasting respiratory quotient in lactating compared with nonlactating women (0.82 and 0.85, respectively) (7), as well as no significant differences in respiratory quotient during lactation (10,15,39) have been published.…”
Section: Energy Expenditure During Lactationmentioning
confidence: 99%
“…Printed in USA. © 1999 American Society for Clinical Nutrition Adjustments in energy expenditure and substrate utilization during late pregnancy and lactation and unchanged in other studies (10,15). The effects of body composition and hormonal milieu on metabolic responses to pregnancy and lactation have not been investigated thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for energy-sparing mechanisms is con¯icting. Some authors reported a lower BMR (Guillermo-Tuazon et al, 1992) or an increased muscular ef®ciency (Spurr et al, 1998), while other studies did not show any energetic adaptation as a response to an energy de®cit (Frigerio et al, 1991;Beall et al, 1996;Butte et al, 1997;Ferro-Luzzi et al, 1997). Recently Shetty (1999) has questioned the metabolic adaptation of undernourished people.…”
Section: Introductionmentioning
confidence: 99%